The influence of job motivation, work environment and work discipline on the performance of technical staff - Yanti Oktavia; Ratu Muhdiroh; Iman Taofik; Wahyudi Wahyudi; Ahmad Solihin (Institute of Computer Science (IOCS), 2026)
This study examined the influence of work motivation, work environment, and work discipline on the performance of technical employees at PT Optima Mandiri Globalindo Bekasi, a company specializing in medical equipment calibration services. Although these factors have been widely studied in human resource management research, limited empirical evidence exists regarding their combined effects on technical personnel working in highly regulated calibration industries. This research addresses that gap by providing evidence from a sector that demands high levels of accuracy, compliance, and professional responsibility. A quantitative approach was employed using a saturated sampling technique involving all 68 technical employees. Data were collected through structured questionnaires and analyzed using multiple linear regression, supported by validity, reliability, and classical assumption tests. The findings revealed that work motivation, work environment, and work discipline positively and significantly affect employee performance. The regression results showed that work motivation (β = 0.420), work environment (β = 0.603), and work discipline (β = 0.422) significantly contributed to performance improvement, with the work environment emerging as the most influential factor. Simultaneously, the variables significantly affected employee performance (F = 100.531; p < 0.001). The Adjusted R² value of 0.818 indicates that 81.8% of employee performance variation is explained by the model. The study contributes to human resource management literature and provides practical guidance for improving organizational performance through motivation, workplace conditions, and discipline enhancement.